Appropriations habitantes dans les espaces intermédiaires des grands ensembles toulousains - Audrey Courbebaisse (Projets de Paysage)
Intermediate spaces, free and open, which often have an ambiguous legal status, are characteristic of the large housing estates built in the second half of the 20th century. They also provide a support for the appropriation by the inhabitants of their living space and a setting in which to express creativity. The article hypothesises that these appropriations, both individual and collective, embody a certain relationship to space, but also to the other and to society. In this respect, they include a political dimension. This is what we propose to examine in three large housing estates in Toulouse. In what way do the inhabitants’ appropriations of intermediate spaces constitute a political act and to what spatial and social rationale do they correspond? The first part introduces the body of research and proposes a theoretical analysis of the appropriations of inhabitants in these large housing estates. The second part focuses on the spatial configurations that are conducive to the inhabitants expressing themselves and the conditions in which individual and collective appropriations acquire a political dimension. Finally, the last part presents a possible typology of ways of forming a landscape with the intermediate spaces of large housing estates.